Feasibility of Virtual Research Visits in Fox Trial Finder - Dorsey, E. Ray; Wagner, Joseph D.; Bull, Michael T.; Rizzieri, Ashley; Grischkan, Justin; Achey, Meredith A.; Sherer, Todd; Chowdhury, Sohini; Meunier, Claire; Cappelletti, Lily; Rocker, Charlotte; Richard, Irene H.; et al. (Journal of Parkinson's disease, 2015)
Abstract Background: Fox Trial Finder is an online registry for individuals with and without Parkinson disease (PD) interested in participating in PD research. However, distance or disability could prevent such individuals from participating in traditional, clinic-based research at major centers. Objective: Use videoconferencing to connect participants to specialists to: (1) demonstrate feasibility of virtual research visits within this population (2) collect phenotypic data of the participants, (3) validate self-reported diagnosis, and (4) gauge interest in virtual research visits. Methods: We solicited volunteers throughout the United States through Fox Trial Finder. Interested individuals with PD provided consent, were given web cameras if needed, completed baseline surveys, and downloaded videoconferencing software remotely. Participants had a test connection and assessment appointment which included the Montreal Cognitive Assessment (MoCA), then a virtual research visit with a neurologist who reviewed their history and assessed their PD using a modified Movement Disorders Society Unified Parkinson’s Disease Rating Scale. Neurologists assessed PD diagnosis and symptomatology. Physicians and participants were surveyed about their experience. Results: Of 204 individuals who consented, 166 (81% ) individuals from 39 states completed all visits. The mean age was 62 and mean disease duration was 8.0 years. Mean MoCA score was 26.5, and mean modified MDS-UPDRS motor score was 22.8 (out of a possible 124). Neurologists judged PD as the most likely diagnosis in 97% of cases. Overall satisfaction with the visits was 79% (satisfied or very satisfied) among neurologists and 93% among participants. Conclusions: Through virtual research visits, neurologists engaged, characterized, and validated self-reported diagnosis in individuals with PD over a broad geography. This model may facilitate future research participation.